Genotoxic Maillard byproducts in current phytopharmaceutical preparations of Echinodorus grandiflorus - ELISANGELA C. LIMA-DELLAMORA; KASSIA C.V. WALDHELM; ADRIANA M. ALVES; CLAUDIA A.S. LAGE; ALVARO A.C. LEITÃO; RICARDO M. KUSTER (Anais da Academia Brasileira de Ciências, 2014)
Extracts of Echinodorus grandiflorus obtained from dried leaves by three different techniques were evaluated by bacterial lysogenic induction assay (Inductest) in relation to their genotoxic properties. Before being added to test cultures, extracts were sterilized either by steam sterilization or ultraviolet light. Only the extracts prepared by infusion and steam sterilized have shown genotoxic activity. The phytochemical analysis revealed the presence of the flavonoids isovitexin, isoorientin, swertisin and swertiajaponin, isolated from a genotoxic fraction. They were assayed separately and tested negative in the Inductest protocol. The development of browning color and sweet smell in extracts submitted to heat, prompted further chemical analysis in search for Maillard's reaction precursors. Several aminoacids and reducing sugars were cast in the extract. The presence of characteristic Maillard's melanoidins products was determined by spectrophotometry in the visible region and the inhibition of this reaction was observed when its characteristic inhibitor, sodium bisulfite, was added prior to heating. Remarkably, this is the first paper reporting on the appearance of such compounds in a phytomedicine preparation under a current phytopharmaceutical procedure. The genotoxic activity of such heat-prepared infusions imply in some risk of developing degenerative diseases for patients in long-term, uncontrolled use of such phytomedicines.